OTX2 represses sister cell fate choices in the developing retina to promote photoreceptor specification - Miruna Georgiana Ghinia Tegla; Diego F Buenaventura; Diana Y Kim; Cassandra Thakurdin; Kevin C Gonzalez; Mark M Emerson (eLife, 2020)
During vertebrate retinal development, subsets of progenitor cells generate progeny in a non-stochastic manner, suggesting that these decisions are tightly regulated. However, the gene-regulatory network components that are functionally important in these progenitor cells are largely unknown. Here we identify a functional role for the OTX2 transcription factor in this process. CRISPR/Cas9 gene editing was used to produce somatic mutations of OTX2 in the chick retina and identified similar phenotypes to those observed in human patients. Single cell RNA sequencing was used to determine the functional consequences OTX2 gene editing on the population of cells derived from OTX2-expressing retinal progenitor cells. This confirmed that OTX2 is required for the generation of photoreceptors, but also for repression of specific retinal fates and alternative gene regulatory networks. These include specific subtypes of retinal ganglion and horizontal cells, suggesting that in this context, OTX2 functions to repress sister cell fate choices.